Perceived Versus Actual Risk of Type 2 Diabetes by Race and Ethnicity. Issue 3 (June 2018) - Yang, Kyeongra; Baniak, Lynn M.; Imes, Christopher C.; Choi, JiYeon; Chasens, Eileen R.
Purpose: The purpose of this study was to examine associations between perceived risk and actual risk of type 2 diabetes by race and/or ethnicity. Methods: The study sample included 10 999 adults from the 2011 to 2014 National Health and Nutrition Examination Survey. Sociodemographic, clinical, and behavioral data were collected using interviews and physical examinations. Participants were asked if they felt at risk for diabetes or prediabetes and then asked the reasons why. Data analyses were conducted with SAS to properly analyze complex survey data. Results: About 86% of the sample (n = 9496) answered the risk perception question for diabetes, and among those, 28.4% indicated having a high perceived risk. Among this subsample, 38.3% were identified as having an actual risk for prediabetes or diabetes according to the American Diabetes Association guidelines. Across all race groups, the most frequently reported risk factors participants believed to contribute to their risk for diabetes were family history of diabetes, obesity, and poor diet habits. When the percentage of participants with an actual risk factor who correctly perceived it as a risk factor was examined, fewer Asians correctly perceived weight status and physical activity level as a risk for diabetes in contrast to the other racial/ethnic groups. Conclusions: Our study showed that when perception was compared to actual risks, associations differed statistically by race. It will be essential to discuss their risk perception to proper screening for diabetes and relevant lifestyle modifications to prevent and delay the onset of diabetes.